Transit life : how commuting is transforming our cities - Bissell, David, 1982- (Urban and industrial environments, 2018)
"Commuting is a significant segment of everyday life and as city populations and boundaries expand, so do commutes. Transit Life is the first book to explore how commuting is transforming life in the twenty-first century city. Through rich and evocative accounts of commuting experiences, the book shows how everyday journeys through cities are changing the way that people negotiate their work-life balance; they are putting all manner of physical and emotional demands on the people involved; they are changing the nature of people's relationships; and they are creating new forms of enablement and constraint. Contrasting with more conventional quantitative approaches, Transit Life introduces a novel set of methods and ideas that can help us to understanding how commuting is generating new and unexpected forms of social change through the way that people socialize; the way that people work; the way that people use their leisure time; and the way that people inhabit the city."--Provided by publisher